Close facial emotions enhance physiological responses and facilitate perceptual discrimination. (May 2021) - Dureux, Audrey; Blini, Elvio; Grandi, Laura Clara; Bogdanova, Olena; Desoche, Clément; Farnè, Alessandro; Hadj-Bouziane, Fadila
Abstract: Accumulating evidence indicates that the peripersonal space (PPS) constitutes a privileged area for efficient processing of proximal stimuli, allowing to flexibly adapt our behavior both to the physical and social environment. Whether and how behavioral and physiological signatures of PPS relate to each other in emotional contexts remains, though, elusive. Here, we addressed this question by having participants to discriminate male from female faces depicting different emotions (happiness, anger or neutral) and presented at different distances (50 cm–300 cm) while we measured the reaction time and accuracy of their responses, as well as pupillary diameter, heart rate and heart rate variability. Results showed facilitation of participants' performances (i.e., faster response time) when faces were presented close compared to far from the participants, even when controlling for retinal size across distances. These behavioral effects were accompanied by significant modulation of participants' physiological indexes when faces were presented in PPS. Interestingly, both PPS representation and physiological signals were affected by features of the seen faces such as the emotional valence, its sex and the participants' sex, revealing the profound impact of social context onto the autonomic state and behavior within PPS. Together, these findings suggest that both external and internal signals contribute in shaping PPS representation.